The Education Policy as Public Policy - Nuriyah, Dewi Shinta; Azani , Fajriyan Megawati; Duryat, Masduki (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Education is a fundamental right of every citizen and is also categorized as a public good, which the state is responsible for fulfilling. Therefore, education policy cannot be separated from the framework of public policy. This article examines the formulation, implementation, and evaluation processes of education policy from a public policy perspective, while also linking it to the role of educational management on a macro scale. Using a descriptive-qualitative approach, this article discusses the principles of educational management, the stages of policy formation, and the challenges faced during its implementation in Indonesia. The findings indicate that education policy, as an integral part of public policy, requires multi-stakeholder involvement and a multidisciplinary approach in order to respond to societal needs fairly and equitably. It is hoped that this study will contribute to a better understanding and strengthening of education policies that are more responsive and oriented toward social justice.